It’s all about attitude : how eight educators view and value preschool visual art education - Michelle Sonia Horne 1967- (2015)
This research examines educators’ views about visual art education in preschool settings. In Iceland today one third of staff in most preschools are qualified preschool teachers while the other two thirds have some other kind of education and/or working experience. Even though the group has diverse backgrounds, all staff ought to work in accordance with the National Curriculum Guide for Preschools. Eight participants from four preschools in the greater Reykjavík area, five general staff and three holding managerial positions, were purposefully selected based on their education, age, position and experience with working with children in preschool settings. The intent was to represent the diversity of educators’ backgrounds to see if that influenced how they view and value their work in teaching preschool children visual art. This is a qualitative research project which took place between February and April 2014. Open questions were used in the interviews and constant comparative methods chosen for the organization and analysis of data. The results of this research suggest that educators’ attitudes and experience with visual arts play a vital role in how it is being offered in preschools. Participants who have experience working with a creative mentor all agree that their knowledge and approach to teaching art benefit and influence both children and staff in positive ways and thereby increase the quality of art education that is offered in their schools. Participants agreed that continuous learning is beneficial for working in a professional manner, but also mentioned that there had been very few art-related courses available for staff to take part in. Participants were unclear on what children learned from art but were aware that it was important to their education and that in the process it evoked joy and happiness. Þessi rannsókn varpar ljósi á og gefur innsýn í viðhorf starfsfólks til sjónlistir í leikskólum. Einn þriðji starfsfólks leikskóla á Íslandi eru menntaðir leikskólakennarar og þar af leiðandi eru ...